Finding Dorothy [large type] : a novel - Letts, Elizabeth (Random House Large Print, 2019)
Reimagines the story behind the creation of The Wonderful Wizard of Oz" from the perspective of L. Frank Baum's intrepid wife, Maud, whose hardscrabble life on the Dakota prairie inspires her husband's masterpiece and her advocacy of an exploited Judy Garland.